Testing of Metallurgical Equipment on Contact Strength and Wear Resistance; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Malushin N. N.; Valuev D. V. Denis Viktorovich; Valueva A. V. Anna Vladimirovna; Serikbol A. (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen